The Pharmacological Evidences for the Involvement of AhR and GPR35 Receptors in Kynurenic Acid-Mediated Cytokine and Chemokine Secretion by THP-1-Derived Macrophages - Katarzyna Sawa-Wejksza; Jolanta Parada-Turska; Waldemar Turski (Molecules)
Kynurenic acid (KYNA), a tryptophan metabolite, possesses immunomodulatory properties, although the molecular mechanism of this action has not yet been resolved. In the present study, the effects of KYNA on the secretion of selected cytokines and chemokines by macrophages derived from the human THP-1 cell line are investigated. Furthermore, the involvement of the aryl hydrocarbon receptor (AhR) and the G protein-coupled receptor 35 (GPR35) in mediating the effects of KYNA was examined. In lipopolysaccharide (LPS)-stimulated THP-1-derived macrophages, KYNA significantly reduced IL-6 and CCL-2, but increased IL-10 and M-CSF levels. AhR antagonist CH-223191 reduced the KYNA influence on IL-6, CCL-2, and M-CSF production, while the GPR35 antagonist, ML-145, blocked KYNA-induced IL-10 production. Furthermore, it was shown that THP-1 derived macrophages were capable of synthesizing and releasing KYNA and that its production was increased in the presence of LPS. These findings suggest that THP-1-derived macrophages are a source of KYNA and that KYNA modulates inflammatory responses predominantly through AhR and GPR35 receptors. Our study provides further evidence for the involvement of macrophages in immunomodulatory processes that are dependent on AhR and GPR35 receptors, as well as the potential role of KYNA in these phenomena.